PRONAF como instrumento de atuação do Estado no espaço rural do semiárido piauiense - Alencar, Maria Tereza de (2010)
The research has as central objective to analyze the contribution of Pronaf to the alterations of the rural space of Piauiense Semiarid, through its line of actions as public policy addressed to familiar agriculture, supported by the following assumptions: understanding the role of the state in capitalist production and regionalization of space and the changes in rural areas and their relations with the urban space through public policies. Discussion of public policies to familiar agriculture, in the case of Pronaf. Analysis of Pronaf actuation in Aglomerado 12, territorial and empirical clipping of the research, considering its objectives, line of actions and categories of producers. Reflection about the program actuation face to the reality of Piauiense Semiarid, its contribution to the generation of work and income, diversity of production, agrarian reformation and the insertion of the familiar farmer in the market. To obtain the primary data, it was used a structured interview with pronafians familiar farmers in the 14 towns of Aglomerado 12, with mediator agents of the program in the State, in the Territory and in the Aglomerado. The data from secondary source about the program were obtained from the SAF website, MDA delegacy of Piauí, in the State Executive Secretary of Pronaf, in the Plan of Action to the Development of Parnaiba Basin, in the document Piaui Regional Scenery Project and in the Plan of Territorial Sustainable Development of Guaribas Valley Territory. To founding the work, a bibliographic research was undertaken with the reading of several authors that approach the subject, besides the research in official documents of the federal and state government. It was concluded that, although the Pronaf is not developing according to its objectives and lines of action in the Piauiense Semiarid, the program is contributing to alterations in the rural space of Aglomerado 12, through the on-lending to familiar farmers, allowing them to acquire products and use services that were unavailable to them before. The rural space is more dynamic as a bigger circulation of money, people and goods is taking place in a relationship of interdependence and complementarities with the urban space in the Aglomerado and in the Territory. However, the familiar farmers still continue dependent on merchant middlemen, who get the profit of the products acquired at low prices and exploiting the familiar labor, that is still jobless even with the Pronaf resources, and, indirectly, benefit themselves from the program resources.